PENGAWASAN PERTAMBANGAN LIAR BAHAN GALIAN BATUAN (GALIAN C) DI KABUPATEN KAMPAR - Rahmawati, Risky; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
We still find many illegal mining that is happenedin Kampar regency espectial in Tapung sub-district,most of all mining in Tapung sub-district do not have business permit based on data do not have bisiness permit most in Tapung sub-district. Department of Energy and Mineral Resources together with judicial team controlling illegal mining in Kampar sub-district, the problem in this research is how to controlling olegal mining of minerals rocks (entrenchment C) in Kampar regency and the factor which influence it.Theoretical consept that reaserches use is repressive control theory according to Manullang (2008) with indicator to set of measuring instruments (standard), assessment action and take corrective action. Whereas of factors which influence it researcher uses descriptive qualitative method, then presentation and data can be described by using interview , observation and get the conclusion.The result of research can be conclude that the contloll of illegal mining in Kampar regency especially in Tapung sub-district still not running maximumly, still have limitation in standard setting, assessment and remedial action has not run maximumly, and the factors that influence the control of illegal.Keywords: Control, illegal mining